Urine excretion of C3dg and sC5b-9 coincide with proteinuria and development of preeclampsia in pregnant women with type-1 diabetes. Issue 2 (February 2023) - Isaksson, Gustaf L.; Nielsen, Lise H.; Palarasah, Yaseelan; Jensen, Dorte M.; Andersen, Lise L. T.; Madsen, Kirsten; Bistrup, Claus; Jørgensen, Jan S.; Ovesen, Per G.; Jensen, Boye L.
Abstract : Objective: Pregnant women with type-1 diabetes have an increased risk of preeclampsia with kidney injury and cardiovascular complications. Urine excretion of plasmin and soluble membrane attack complex (sC5b-9) is elevated in severe preeclampsia. We hypothesized a coupling between these events and that active plasmin promotes intratubular complement activation and membrane deposition. Methods: Stored urine and plasma samples from pregnant women with type-1 diabetes ( n  = 88) collected at gestational weeks 12, 20, 28, 32, 36 and 38 were used. In the cohort, 14 women developed preeclampsia and were compared with 16 nonpreeclampsia controls. Results: Urine C3dg and sC5b-9-associated C9 neoantigen/creatinine ratios increased and were significantly higher in women who developed preeclampsia. Plasma concentrations did not change with gestation. Urine plasmin(ogen) correlated to urine C3dg ( r  = 0.51, P  < 0.001) and C9 neoantigen ( r  = 0.68, P  < 0.001); urine albumin correlated to C3dg ( r  = 0.44, P  < 0.001) and C9 ( r  = 0.59, P  < 0.001). Membrane-associated C3dg and C9 neoantigen was detected in urinary extracellular vesicles from patients but not controls at 36 weeks. Receiver operating characteristic curves showed that C3dg and C9 neoantigen were inferior to albumin as predictive biomarkers for preeclampsia. Conclusion: In preeclampsia, urinary excretion of activated complement relates significantly to albuminuria and to plasmin(ogen) but not to activation in plasma. Intratubular complement activation in preeclampsia is a postfiltration event tightly related to proteinuria/plasminogenuria and a possible mechanistic link to cellular damage and kidney injury. Abstract :